Effect of Alfacalcidol on Bone and Calcium Metabolism in Elderly Women - Naka, Hiroshi; Nishizawa, Yoshiki; Saito, Shinichi; Miki, Takami; Morii, Hirotoshi; Nakatsuka, Kiyoshi; Kitatani, Kayoko (Nihon Rōnen Igakkai zasshi, 2002)
Oral administration of active vitamin D3 can reduce the loss of bone mass and the incidence of fractures in patients with osteoporosis in Japan. We conducted a prospective study to confirm the effects of 1α(OH)D3 (Alfacalcidol, Alfarol Chugai Tokyo) on bone and calcium metabolism in elderly women with osteoporosis. Enrolled in the present study were 16 elderly osteoporosis women aged 72.6±4.5 years to whom 1μg of 1α(OH)D3 was administered daily. Fasting blood and urine were obtained at baseline, 1 week, 4 weeks, 12 weeks and 24 weeks after the treatment. Monitored parameters were vitamin D metabolites, intact-PTH, bone alkaline phosphatase (BAP), osteocalcin (OC), deoxypyridinoline (DPD) and pyridiuium crosslinked type I collagen telopeptides (CTx). Serum 1α, 25(OH)2D and PTH levels were significantly increased (p<0.01) and decreased (p<0.05), respectively at 1 week after commencing administration. There was a significant decrease of DPD (p<0.05) at 12 weeks after commencing administration compared to the baseline levels. Serum levels of BAP and OC were found elevated at 1 week, and decreased at 12 weeks. In conclusion, the present study clinically confirmed that 1α(OH)D3 stimulates bone formation in vitro. Long-term administration of 1α(OH)D3 indirectly suppressed bone resorption through the suppression of parathyroid function in the elderly.